Collegiality Washing? New Translations of Collegial Practices - Kerstin Sahlin; Ulla Eriksson-Zetterquist (Emerald Publishing Limited, 2023)
Over the past few decades, university reforms in line with management and enterprise ideals have been well documented. Changes in the ideals underlying the missions of universities have led to changes in their modes of governing and organizing, which in turn drive further transformation of their missions. One set of reforms in Swedish higher education has been the dissolution of collegial bodies and procedures. At the same time, in recent years, we have witnessed an increased interest in collegiality and a reintroduction of collegial bodies and procedures. New translations of collegiality appear not only in how universities are organized, but also in other core aspects of research and higher education. We review examples of peer reviewing, research assessment, and direct recruitment of professors and ask: Can these new translations of collegiality be understood as a revitalization of collegiality, or is it – to draw a parallel with greenwashing – rather a matter of collegiality-washing?
10.1108/S0733-558X20230000087007; 10.1108/S0733-558X20230000087007; Revitalizing Collegiality: Restoring Faculty Authority in Universities; EBP099697181